Acyl-CoA dehydrogenase long chain acts as a tumor-suppressive factor in lung adenocarcinoma progression - Tingju Wei; Guowei Fu; Junjie Zhao; Fengan Cao; Danfeng Guo (Cell Adhesion & Migration)
This study investigated the role of long-chain acyl-CoA dehydrogenase (ACADL) in lung adenocarcinoma (LUAD). ACADL was significantly downregulated in human LUAD tissues compared to normal lung tissues. In vitro, ectopic expression of ACADL in murine LLC cells decreased cell viability, migration, and invasion, while ACADL knockdown exhibited the opposite effect. In vivo, ACADL overexpression impeded tumor growth and metastasis. Mechanistically, ACADL hindered tumor progression by inducing cell cycle arrest, promoting apoptosis, and suppressing the epithelial-mesenchymal transition (EMT) process. These findings suggest ACADL acts as a tumor suppressor in LUAD progression.